Pengaruh Digital Marketing terhadap Minat Beli Konsumen Pada Jasa Tour dan Travel Mega Trans Holiday - Dewi Rosita; Elgi Manansyah; Widwi Handari Adji (Universitas Batanghari Jambi, 2022)
This study aims to determine how the influence of digital marketing on consumer buying interest in mega trans Bandung tour and travel services, and what are the advantages and disadvantages of digital marketing for business people and customers. In this study, descriptive research is combined with quantitative research by providing data obtained through quantitative and statistical methods. Interviews and surveys were used to collect data for this investigation. The results and analysis show that the digital marketing variable has a positive and large effect on consumer buying interest, with a strong influence because the rest is influenced by other variables that are not included in this research model. Having a well-designed website or app to attract and engage potential clients is critical to digital marketing success.